Peningkatan Daya Kecambah dan Pertumbuhan Benih Kayu Manis (Cinnamomum burmanii) dengan Berbagai Media Tumbuh - Suryani, Erma; Idris, Herwita; Melati, M (Journal Galung Tropika, 2020)
Seeding media have a large role in helping to accelerate germination and seed will have a different response to certain media. Seeding media is needed so that the potential viability of seeds can be optimal. Media in nurseries have a large role in helping accelerate budding. The study was conducted in the greenhouse of the Laing Solok Experimental Garden, West Sumatra. The research aimed to know the composition of the media that can improve the viability of cinnamon (Cinnamomum burmanii) seeds. The study was arranged in a completely randomized design with 7 treatments: wastes ash distillation of citronella, burnt husk, sawdust, soil + wastes ash distillation citronella, ground + burnt husk, sand, and soil. All experiment treatment were repeated 5 times. Each treatment was used 30 seeds of cinnamon with a spacing of 5 x 5 cm. The parameters observed included percentage of growth, vegetative growth (seed height, number of leaves, leaf length and leaf width), root length, number of roots, biomass (wet and dry weight of seeds, root wet and dry weight). The results showed that the best growing media for recalcitrant cinnamon seeds were sawdust and soil + ash of citronella refining waste. The growth percentage of the two media were 76.00% and 64.00% respectively, the best vegetative growth, with the wet weight of the seeds respectively 0.74 g and 0.71 g, root wet weight 0.19 and 0.13 g, seed dry weight of 0.25 and 0.23 g, root dry weight of 0.11 and 0.06 g. The best total leaf chlorophill content in both types of media was 0.026 and 0.034.